2011
DOI: 10.1007/s10549-011-1605-0
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-like growth factor-1 receptor gene expression is associated with survival in breast cancer: a comprehensive analysis of gene copy number, mRNA and protein expression

Abstract: Insulin-like growth factor-1 receptor (IGF1R) plays a key role in the initiation and progression of breast cancer. However, its prognostic relevance to breast cancer patients has long been a matter of debate. In a series of 325 primary invasive breast cancer patients, we performed a comprehensive analysis of IGF1R at the levels of gene copy number, mRNA expression and protein expression. The relationship between the IGF1R status and the clinicopathological characteristics and prognosis was evaluated. IGF1R mRN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
35
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 32 publications
(33 reference statements)
2
35
0
3
Order By: Relevance
“…A study using a rabbit polyclonal antibody (SC713) showed that in 429 patients with stage I–III HER2+ breast cancer, 26% demonstrated IGF1R expression (Allred Score ≥ 7) and only 9% of HER2-enriched tumors had IGF1R expression (Allred score ≥ 7)(47). A study that utilized the same polyclonal antibody as our study (directed against the β subunit of IGF1R) showed that 65% of 297 unselected breast cancers did not have IGF1R protein expression and 3% of the cases had 3+ staining(39). This same antibody detected membrane IGF1R (when exceeded cytoplasmic staining) in 13.8% of 160 HER2+ breast cancers(25).…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…A study using a rabbit polyclonal antibody (SC713) showed that in 429 patients with stage I–III HER2+ breast cancer, 26% demonstrated IGF1R expression (Allred Score ≥ 7) and only 9% of HER2-enriched tumors had IGF1R expression (Allred score ≥ 7)(47). A study that utilized the same polyclonal antibody as our study (directed against the β subunit of IGF1R) showed that 65% of 297 unselected breast cancers did not have IGF1R protein expression and 3% of the cases had 3+ staining(39). This same antibody detected membrane IGF1R (when exceeded cytoplasmic staining) in 13.8% of 160 HER2+ breast cancers(25).…”
Section: Discussionmentioning
confidence: 79%
“…However, other radioimmunoassay studies have reported IGF1R as a favorable prognostic factor(41, 43) and although IGF1R levels were ten-fold higher in breast cancer than in normal breast, IGF1R levels were higher in a low-risk breast cancer group(44). Recent univariate analyses demonstrated that both mRNA levels and protein expression were associated with favorable prognosis, a longer breast cancer–specific survival (BCSS), but in the HER2 subtype, IGF1R protein was not significantly associated with BCSS or relapse-free survival(39). The prognostic significance of IGF1R expression may be then dependent on the molecular subtype of breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…However, its prognostic value is controversial depending on the sites of carcinoma [4,17,18,19,20,21,22]. Many reports suggested that IGF1R expression correlated with poor survival in breast cancer [18,23,24]. In contrast, Fu et al [23] described that IGF1R mRNA expression was significantly higher in patients with favorable clinicopathologic parameters.…”
Section: Discussionmentioning
confidence: 99%
“…Many reports suggested that IGF1R expression correlated with poor survival in breast cancer [18,23,24]. In contrast, Fu et al [23] described that IGF1R mRNA expression was significantly higher in patients with favorable clinicopathologic parameters. In gallbladder cancer, tumors with less than 50% of IGF1R immunoreactions showed a significantly worse prognosis [19].…”
Section: Discussionmentioning
confidence: 99%
“…A positive energy balance over time may promote breast cancer growth (1)(2)(3)(4)(5)(6). Potential mechanisms linking a positive energy balance to breast cancer risk and prognosis include elevated levels of circulating or tissue estrogens, insulin, insulin-like growth factor-1 (IGF-1) and low-grade chronic inflammation, as these factors are known to promote cell growth and inhibit apoptosis (1;2;2;3;3;5;7).…”
Section: Introductionmentioning
confidence: 99%